Spirituality in the context of nonverbal autism: practical and theological considerations - Hills, Karenne (Practical theology, 2019)
Traditionally, religious practices and teaching provide guidance for spiritual awareness. The concept of Imago Dei is fundamental to religious and theological belief, however its relevance to people with disabilities is debated. This paper underpins a broader research study exploring the spirituality of people unable to express a belief or understanding of orthodox religion. This will be explored alongside people with severe autism, who are unable to communicate verbally. Spirituality adopts a characteristic language, often expressed by music, metaphor or symbolism. Therefore, a spirituality that is not dependent on language for expression or validation amongst people with nonverbal autism is likely. Currently no research exists that explores the spirituality of this population, which has serious implications concerning the adequacy of current service provision and their inclusion into faith communities. In light of the growing numbers of autism diagnoses, the spiritual needs and expressions of this population require urgent attention.